THE INFLUENCE OF LEADERSHIP STYLE AND WORK STRESS ON ELEMENTARY SCHOOL TEACHER PERFORMANCE - YULIASIH, Tanti; BUNYAMIN, Bunyamin; FITRIANI, Somariah (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
The purpose of this study is to investigate: (1) The Effect of the Principal's Leadership Style on the Performance of Teacher Teachers. (2) The Effect of Work Stress on the Performance of Teacher Teachers. (3) The Effect of Leadership Style on Elementary Teacher's Work Stress. The population referred to in this study was all elementary school teachers of the 5 Korwil District of Pinang Tangerang City, totaling 164 teachers, the sample was 116 teachers taken randomly. The analysis technique used is a path analysis. Based on the results of the study and discussion, it can be concluded a number of important things as follows: 1) There is a positive and significant direct influence on the principal's leadership style on the performance of the Teacher. This is also evidenced from the results of tcount > ttable (23,497 > 1,981) and the path coefficient value of 0,973. 2) There is a positive and significant direct influence on work stress on the performance of the Teacher. This is also evidenced from the results of tcount > ttable (-2.788 > 1,981) and the path coefficient value of -0.129. 3) There is a direct and significant direct influence on the principal's leadership style on the work stress. This is evident from the results of the value of tcount > ttable (20,723 > 1,981) and the path coefficient value of 0.889. with sig. (2-tailed) of 0.002. This means that the principal's leadership style with work stress has a significant relationship and in the weak category.